Speaking truth to power - Hill, Anita (New York : Doubleday, 1997)
After her astonishing testimony in the Clarence Thomas hearings, Anita Hill ceased to be a private citizen and became a public figure at the center of an intense national debate on how men and women relate to each other in the workplace
Includes index.
Keywords: Hill, Anita; Women lawyers -- United States -- Biography; Sexual harassment of women -- Law and legislation -- United States